Monovalent Maleimide Functionalization of Gold Nanoparticles Via Copper-Free Click Chemistry - D. J., Nieves; N. S., Azmi; R., Xu; R., Levy; E. A., Yates; D. G., Fernig (2014)
A single maleimide was installed onto the self-assembled monolayer of gold nanoparticles by copper-free click chemistry. Simple covalent biofunctionalisation is demonstrated by coupling fibroblast growth factor 2 and an oligosaccharide in a 1 : 1 stoichiometry by thiol-Michael addition.